RADT-26. PATTERNS OF RECURRENCE IN PATIENTS TREATED WITH RE-IRRADIATION FOR RECURRENT HIGH-GRADE GLIOMA. (14th November 2022) - Datta, Debanjali; Dasgupta, Archya; Meena, Lilawati; Chatterjee, Abhishek; Sahu, Arpita; Chaudhari, Amit; Joshi, Kishore; Puranik, Ameya; Rangarajan, Venkatesh; Singh, Vikas; Shetty, Prakash; Moiyadi, Aliasgar; et al.
Abstract: Purpose/Objective(s): Re-irradiation (ReRT) is often used to treat recurrent high grade glioma (HGG). There is limited literature regarding the patterns of recurrence following ReRT, which was investigated in the current study. Materials/METHODS: Patients with available radiation (RT) contours, dosimetry, and imaging-based evidence of recurrence were included in the retrospective study. All patients were treated with fractionated RT using conformal technique. Recurrence was documented as per decision in tumor board based on imaging with magnetic resonance imaging (MRI) or Flouroethyl-L-Tyrosine (FET) positron emission tomography (PET), which was registered with the planning CT. Failure patterns were classified as in-field, marginal, and out-field as decided by >50% recurrence volume within 95%, 20-95%, and outside 20% isodose lines, respectively. RESULTS: Study population included 37 patients treated with median dose of 54 Gy (range 50.4-54 Gy). Before ReRT, 92% patients had undergone surgery (biopsy in 3, gross total resection in 9, subtotal resection in 22), 62% received concurrent chemo with ReRT, and 49% received maintenance chemotherapy. Median time to recurrence was 9 months (7-16 months, median 10 and 8 months respectively for in-field and marginal/out-field recurrence). In-field, marginal, and out-field recurrence were seen in 24 (65%), 10 (27%), and 3 (8%), respectively. Recurrence mapping was done using MRI, PET, or both in 27, 3, and 7, respectively. Of 24 patients with in-field recurrence, 8 and 16 had disease volume within gross tumor volume and clinical target volume, respectively. 2 patients had leptomeningeal dissemination (1 with majority of recurrence volume in-field and 1 with marginal failure in addition to metastatic disease). CONCLUSION: Following ReRT for HGG, the majority of recurrence was in the high dose region, suggesting the use of conservative target volumes. Future studies are required for feasibility of dose-escalation to improve control rates, particularly in patients with long intervals from first course of RT.